Optimización de la celda flexible de manufactura didáctica de la Universidad de América a partir del mejoramiento de la automatización actualmente implementada. (2021)
In the area of ​​industrial automation there are manufacturing systems, characterized by manufacturing products in an agile and precise way, but when an industry decides to provide these services, they have to resort to a technological update of the systems that are currently implemented, applying the different levels of automation existing in the CIM pyramid. Taking into account the above, there is great importance in acquiring knowledge based on the correct handling of manufacturing systems, since there is an exponential demand for qualified personnel to perform tasks of this nature.